Edward Said and the Margins - Thomas, Tom (Text Matters: A Journal of Literature, Theory and Culture, 2012)
Edward Said was the quintessential intellectual of the last quarter of the twentieth century. Commonly celebrated as the founding figure of postcolonialism, his critical oeuvre spans varied terrain. The very strength of his critique lies in these diverse tributaries of thought. Crossing borders and boundaries incessantly, Said’s intellectual project celebrates the culture of resistance while opposing doctrinaire rhetoric. The paper tries to journey along the multifarious “margins” of discourses that crop up in Said. “In-between” spaces have to be investigated for their radical potential, while daring to “transgress” has its own dangers. Said unmasks the unholy nexus between knowledge and power in the mapping of the “Orient” that abetted the colonial enterprise. His contrapuntal readings of literary texts reveal the ubiquitous presence of imperial empire. Consequently, voices from the margins spur counter narratives and “writing back” in the postcolonial condition. Intellectuals in exile tend to be “marginal” and this location helps in looking at the two or even three sides of an issue. Questions of identity, selfhood, nationality, politics, memory, history, representation, geography, homeland, anxieties of influence are dealt with in the paper. The intertwining of the personal and the political occurs in Said. “Memory” is the only hope for resuscitating a “lost world” and battling the accompanying sense of “loss” and “despair” infused in both individuals and communities alike. The paper tries to address how “border crossing” and the “coalescing of margins” create an interdisciplinary breadth in Said, which resist categorization. The “centre/margin” binary is problematized by acknowledging the presence of “many voices,” “polyphony” being a favourite concept of Said. Music gave to him metaphors for human emancipation, while “transgression” was vital. His acknowledgement and assimilation of fellow critics is also mentioned. Beyond enunciating insider-outsider distinctions, Said tried to cultivate knowledge as a bridge between different interests and locations.